2017
DOI: 10.1038/ncomms16051
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the critical thickness of electron hybridization in spintronics materials

Abstract: In the rapidly growing field of spintronics, simultaneous control of electronic and magnetic properties is essential, and the perspective of building novel phases is directly linked to the control of tuning parameters, for example, thickness and doping. Looking at the relevant effects in interface-driven spintronics, the reduced symmetry at a surface and interface corresponds to a severe modification of the overlap of electron orbitals, that is, to a change of electron hybridization. Here we report a chemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 54 publications
3
23
0
Order By: Relevance
“…In order to probe the dynamics of the specific electronic structure, we performed chemically and magnetically sensitive pump-probe Hard X-ray Photoemission Spectroscopy (HAXPES) experiments. HAXPES guarantees bulk sensitivity (up to an integration depth of 10 nm [41]), removing uncertainties arising from any surface effects [42][43][44][45]. Thus, the HAXPES results can be directly compared with those of MOKE in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to probe the dynamics of the specific electronic structure, we performed chemically and magnetically sensitive pump-probe Hard X-ray Photoemission Spectroscopy (HAXPES) experiments. HAXPES guarantees bulk sensitivity (up to an integration depth of 10 nm [41]), removing uncertainties arising from any surface effects [42][43][44][45]. Thus, the HAXPES results can be directly compared with those of MOKE in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…3a, where a distinct satellite is present at a binding energy around 640 eV. Such low binding energy satellites have been observed in HAXPES spectra for many oxide systems: they are spectroscopic fingerprints of the strength of electron delocalization and thus of the metallicity of the oxides [42,[45][46][47][48][49].…”
Section: Resultsmentioning
confidence: 99%
“…Although many techniques are used to characterize the properties of half-metallic materials such as Andreev reflection (27,28), spin-polarized tunneling, spin-polarized photoemission (29), and visible MOKE (3), these all rely on surface measurements. However, device applications require coherence and functionality through a finite nanoscale depth, and bulk and surface properties can be significantly different (30)(31)(32)(33)(34). A strong advantage of using EUV MOKE as a probe of these materials is the larger penetration depth of EUV light, more than twice that of visible light, which can, in addition to providing elemental specificity, probe the magnetization state of the material more deeply inside of a device.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that Cu 2p spectra reflect the dimensionality in the CuO 4 plaquettes [32] and react most sensitively to metal-ligand charge transfer and hybridization [33]. Recently it was shown how Mn 2p spectra reflect hybridization strength, metallicity, and magnetic properties [22].…”
Section: Conventional Photoelectron Spectroscopy Of Buried Ifs Inmentioning
confidence: 99%
“…Consequently, in mixed manganite multilayers a rich 55 variety of electronic phases can be stabilized as a function of 56 the thickness of individual blocks and the temperature [21]. 57 Nevertheless, the origin of the dead-layer formation in LSMO 58 thin films is still under debate [22]. Possible mechanisms 59 likely playing a role are substrate-induced strain and structural 60 distortions [23,24], chemical impurities and vacancies [25], as 61 well as intermixing at the IF [26].…”
Section: Introductionmentioning
confidence: 99%